TRANSFORMASI KINERJA UKM: DAMPAK ORIENTASI KEWIRAUSAHAAN, INOVASI PRODUK, DAN KEMAMPUAN MENYUSUN LAPORAN KEUANGAN - Tiara Syahrani (LPPM UNIVERSITAS BINA INSAN, 2024)
This study aims to demonstrate the influence of entrepreneurial orientation, product innovation, and financial reporting capabilities on the performance of SMEs in Lubuklinggau City. The research addresses issues such as the lack of support from the entrepreneurial ecosystem, including access to capital, business networks, and quality human resources, limitations in research and development for product innovation, and constraints in the ability to prepare accurate financial reports. Primary data were utilized in this study, obtained from questionnaires distributed to printing and garment SMEs in Lubuklinggau City. A total of 50 questionnaires were distributed. The data were analyzed using multiple linear regression analysis with SPSS 23.0. The results show that entrepreneurial orientation has a positive impact on SME performance, product innovation positively affects SME performance, and financial reporting capabilities positively influence SME performance. This study can contribute to improving the entrepreneurial orientation, product innovation, and financial reporting capabilities of printing and garment SMEs in Lubuklinggau City, thereby enhancing their overall performance.